2016
DOI: 10.7554/elife.13571
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophosmin integrates within the nucleolus via multi-modal interactions with proteins displaying R-rich linear motifs and rRNA

Abstract: The nucleolus is a membrane-less organelle formed through liquid-liquid phase separation of its components from the surrounding nucleoplasm. Here, we show that nucleophosmin (NPM1) integrates within the nucleolus via a multi-modal mechanism involving multivalent interactions with proteins containing arginine-rich linear motifs (R-motifs) and ribosomal RNA (rRNA). Importantly, these R-motifs are found in canonical nucleolar localization signals. Based on a novel combination of biophysical approaches, we propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
508
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(529 citation statements)
references
References 70 publications
21
508
0
Order By: Relevance
“…We conclude that the integrity of mature heterochromatin domains relies on weak hydrophobic interactions, and that dimerization and interactions with non-histone binding partners contribute to HP1 immobilization. This is consistent with evidence that networks of multivalent interactions promote demixing in vitro and in vivo 7,19 . We propose that mature heterochromatic domains consist of both immobile (static) and mobile (liquid) HP1a compartments, similar to recent findings for nucleoli 20 .…”
supporting
confidence: 91%
“…We conclude that the integrity of mature heterochromatin domains relies on weak hydrophobic interactions, and that dimerization and interactions with non-histone binding partners contribute to HP1 immobilization. This is consistent with evidence that networks of multivalent interactions promote demixing in vitro and in vivo 7,19 . We propose that mature heterochromatic domains consist of both immobile (static) and mobile (liquid) HP1a compartments, similar to recent findings for nucleoli 20 .…”
supporting
confidence: 91%
“…In somatic cells, NPM1 − one of the NPM2 homologs − undergoes phase separation in a concentration-dependent manner together with the arginine-rich proteins and rRNAs that are required for ribosome biogenesis. This event is critical for structural organization of the somatic nucleoli and, presumably, required to control the activity of ribosome biogenesis (Feric et al, 2016;Holmberg Olausson et al, 2014;Mitrea et al, 2016). In our study, we found that NPM2 has the ability to form a spherical body together with other proteins and RNAs in a concentration-dependent manner.…”
Section: (N>3 Each) (B) Npm2 Protein Expression Levels Insupporting
confidence: 48%
“…Because of the complexity of biochemical experiments when using mammalian oocytes, there are few biochemical data of mammalian NPM2 to specify its molecular function. However, one can speculate about the function of NPM2 by comparing it to NPM1 in somatic cells and to nucleoplasmin-like protein (NPL) in Drosophila, since both proteins have the conserved region of the NPM-core domain and also form a spherical body (Liu et al, 2006;Mitrea et al, 2016). For example, NPM1, has the ability to bind to the centromere-specific nucleosome CENP-A and is required for proper kinetochore and microtubule attachments (Amin et al, 2008;Dunleavy et al, 2009;Foltz et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As a histone chaperone, NPM1 binds most efficiently to acetylated H3/H4 heterodimers and, as mentioned above, is able to promote the activities of nucleosome remodeling complexes and to support transcription and chromatin packaging activities (Okuwaki et al 2001;Swaminathan et al 2005). The ability of NPM1 to interact with highly positive sequences, along with its oligomerization activity have D r a f t 9 led several groups to propose that NPM1 may be the scaffolding protein responsible for retention of proteins containing arginine/lysine-rich nucleolar localization signals (NoLSs) within the nucleolus (Emmott and Hiscox 2009;Li et al 1996;Mitrea et al 2016). Through its C-terminal regions, NPM1 is able to bind short ssDNA sequences and promote dsDNA strand annealing (Borggrefe et al 1998) and, independently of those functions, to also interact with structured RNAs in response to genotoxic stress (Yang et al 2002).…”
Section: Nucleophosmin and Nucleolin: Two Multifunctional Nucleolar Pmentioning
confidence: 99%